Introducing process management in E-government and healthcare - Helfert, M.; Dzhumalieva, S. (NTU "KhPI", 2008)
The public sector has shown that it has, comparedwith other sectors, a relatively underdeveloped information system structure. In this context the importance of reducing costs and streamlining workflows and processes is ever more recognized. However, despite the importance of process management, currently there are internationally very few guidelines provided for introducing process management in public administration. The objective of this paper is to outline a framework for analyzing process management projects. By using this framework we analyze a system in the public administration of Bulgaria as well as an implementation of a healthcare administration system in Ireland. Our analysis revealed some interesting results. The reasons for failure in public administration are rather content and structural in nature then solely project management issues.

Відкритий сектор економіки має, у порівнянні з іншими секторами, відносно недостатньо розвинену структуру інформаційних систем. У цьому контексті є сенс вважати важливими зниження витрат та спрямлення робочих потоків. Проте, незважаючи на важливість управління процесами, у теперішній час є дуже мало керівних документів, які допомагають впровадити управління процесами у користувальницьку адміністрацію. Мета цієї роботи – дати огляд можливої інфраструктури для аналізу проектів з управління процесами. Шляхом використання цієї інфраструктури ми аналізуємо систему управління у Болгарії та адміністрування охороною здоров'я у Ірландії. Наш аналіз дав деякі цікаві результати.
Keywords: інформаційні системи; управління; охорона здоров'я; адміністрування